Synoptic analysis and physical characterization of an intense storm occurred in the Bauru-SP region - Mattos, Enrique Vieira; Reboita, Michelle Simões; Llopart, Marta Pereira [UNESP]; Enoré, Diego Pereira (Universidade Federal do Rio de Janeiro, 2020)
On May 21, 2017 in the Bauru city in Sao Paulo State were registered several floods and flash floods. The main goal of this work is to understand the synoptic conditions and the physical properties of clouds associated with this thunderstorm. We have used European Centre for Medium Range Weather Forecast Reanalysis (ERA5 e ERA-Interim), surface automated weather station, single-polarization meteorological radar, satellite images and lightning ground station data. The multicell storm presented a linear-shaped format, with several convective cells and have initiated at west region of São Paulo State in an environment with higher Convective Available Potential Energy value (2500 J kg-1). The synoptic environment presented the South Atlantic Subtropical Anti-cyclone displaced eastward of its climatological position and a trough with small amplification with axes from Mato Grosso do Sul to Rio Grande do Sul, which favors the formation of a low-pressure region between southeastern Brazil and Atlantic Ocean. Low Vertically Integrated Liquid Water Content (2 kg m-2) and moderate reflectivity eco (44 dBZ) was observed. The longer duration (1 hour and 23 minutes) of multicell storm inside the radar range, it was probably responsible for the higher accumulative precipitation. The lead-time (23 minutes) between the maximum lightning rate (0.08 lightning per km2 in 7.5 minutes) and news reports, suggested the potential use of lightning for nowcasting proposes. The multicell storm produced a cyclonic mesoscale convective vortex in its polar flank, associated with the comma echo signature; typical characteristic of intense thunderstorms. These results indicated that the combination of synoptic conditions, physical and electrical information are important parameters that could be used for nowcasting.
Análise sinótica e caracterização física de uma tempestade intensa ocorrida na região de Bauru-SP
Keywords: Cloud Microphysics; Flash Flood; Radar